Prevalence of Serological Markers of TORCH Infections in Biliary Atresia and Other Neonatal Cholestatic Disorders - Mostafa Mohamed Sira; Ahmad Mohamed Sira; Ibrahim A Elhenawy; Fatma Omar Khalil (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2016)
Background: Viral infections, congenitally or perinatally acquired, have been associated with neonatal cholestasis. Investigators have suggested a similar link to biliary atresia (BA).   Aim: The aim of the current study is to investigate the prevalence of serological markers of congential infections in BA and other neonatal cholestatic disorders. Methods: This retrospective study included 94 patients with confi rmed diagnosis of BA. A nearly comparable number of patients with cholestasis due to causes other than BA (n = 91) were also recruited and termed non-BA group. The data was retrieved from patients' records. TORCH (toxoplasma, rubella, cytomegalovirus [CMV] and herpes simplex virus [HSV] type 1 and type 2) antibodies (immunoglobulin [Ig] M and IgG) were performed in all the patients using enzyme-linked immunosorbent assay. CMV DNA was detected by polymerase chain reaction (PCR). Results: Both groups were age and sex matched (P>0.05). TORCH IgM antibodies were detedcted in 15.7% of all the study population (8.5% in BA group and 23% in non-BA group), of which CMV was the commonest agent. CMV IgM and CMV DNA by PCR were signifi cantly higher in non-BA group (20.9% and 23% respectively) than in BA group (4.3% and 5.3% respectively). Toxoplasma IgM was positive in only one patient in BA group and rublella IgM was positive only in one patient in the non-BA group. HSV- 1 IgM was found in a total of 4 patients; 3 in BA group and one in non-BA group while HSV-2 IgM was negative in all the patients. CMV infection was the sole incriminated agent in 13 patients (CMV hepatitis), while it was associated with other etiologies such as pregressive familial intrahepatic cholestasis (5 of 29 patients), and intrahepatic biliary paucity (3 of 14 patients). Liver transaminases, prothrombin time and the frequency of  growth failure were signifi cantly higher in non-BA group. Conclusions: TORCH IgM antibodies were detedcted in 8.5% of BA and in 23% of non-BA group, of which CMV was the commonest agent. In addition to CMV hepatitis, CMV infection was associated with other causes of neonatal cholestasis. For that, all cases with neonatal cholestasis should be thoroughly evaluated for other causes, even in cases with demonstrable CMV infection.